(untitled) (CIENCIA Y TECNOLOGÍA AGROPECUARIA, 2025)
Promoting competitiveness and agro-industrial innovation in the canton of Chone - Manabí, influences the growth and socio-economic development of small and large companies that respond to the local demand for goods and services. Therefore, it is essential that the Ecuadorian State reinforces public policies that involve determining factors in the change of the national productive matrix; and the allocation of resources to consolidate the systems of research, science and innovation, agricultural education, infrastructure, promotion, inspection of safety in industrial processes and food safety. This work seeks to rerelate agribusiness and its development in the economy of Chone through a documentary and testimonial analysis to project it diachronically in the regional context, for which a bibliographic review was used that is circumscribed in documentary research supported by the systematic review of bibliographic documents and archives. interviews with key informants on the different stages of agribusiness in the Chone canton, research surveys with agro-industry owners or their descendants that seek to impact the social economy of the local sector and at the national level. Based on this analysis, the research concludes that innovation in the agro-industrial sector of the Chone canton is a determining factor to increase the productivity and competitiveness of micro-enterprises in the locality and therefore in the country, emphasizing that in the micro-region there is a precariousness of the agro-industrial sector caused by local factors and also by global currents.